Understanding Participation in Genetic Research Among Patients With Multiple Sclerosis: The Influences of Ethnicity, Gender, Education, and Age - Cuccaro, Michael L.; Manrique, Clara P.; Quintero, Maria A.; Martinez, Ricardo; McCauley, Jacob L. (Frontiers in Genetics, 2020)
This study examined reasons for participation in a genetic study of risk for Multiple Sclerosis (MS). Our sample consisted of 101 patients diagnosed with MS who were approached about enrolling in the Multiple Sclerosis Genetic Susceptibility Study. Participants were predominantly Hispanic (80%), female (80%), and well educated (71%), having at least some level of college education. Of these 101 individuals who were approached, 95 agreed to participate and are the focus of this report. Among enrollees, the most frequently cited reasons for participation were to find a cure for MS (56%), having MS (46%), and helping future generations (37%). Regression models Comparing ethnic groups, Hispanics endorsed having MS as a reason to participate significantly more frequently than non-Hispanics (HI 52%, non-HI 19%, p=0.015) while non-Hispanics endorsed finding new and better treatments significantly more frequently than Hispanics (Hispanic 17%, non-Hispanic 50%, p=0.003). Among our three age groups, younger individuals endorsed finding a cure for MS significantly more frequently (74% of 18-35 year olds vs. 56% of 36-55 year olds vs. 39% of >55 year olds). Our results suggest that motivations for participation in genetic research vary by ethnicity, and that these influences need to be considered in developing more inclusive programs of disease-related genetic research. This study is particularly timely, as it dovetails with national efforts to seek out, enroll, and engage with the diverse US population through the National Institute of Health’s (NIH) Precision Medicine Initiative Cohort Program.